2017
DOI: 10.1515/vzoo-2017-0025
|View full text |Cite
|
Sign up to set email alerts
|

Preadaptive Stage for Flight Origin

Abstract: Pr eadaptive Stage for Flight Origin. Bogdanovich, I. A. -Bipedalism as a preadaptive stage for bird's fl ight is considered. We attribute the formation of full bipedalism in bird ancestors with pelvic limbs transition from segmental to parasagittal position. Th is transition was fast enough. We can assume that the pectoral limbs freed from the support remained while laterally spaced and gave set of transformations with diff erent degrees of reduction. Th us morphologically "winglike" version of the thoracic l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 22 publications
(35 reference statements)
0
6
0
Order By: Relevance
“…This is most clearly seen in the case of wing-and foot-propelled underwater swimmers. Although both ecological groups share a number of distinctive features, such as posterior position of legs on a long axis of a body (Kurochkin, 1971;Johnsgard, 1987;Ibáñez & Tambussi, 2012), narrow elongated pelvis (Raikow, 1970(Raikow, , 1985Kurochkin, 1971;Bogdanovich, 2003), a great height of the acetabular zone (Ibáñez & Tambussi, 2012;Anten-Houston et al, 2017), low pelvic angles (Anten-Houston et al, 2017) that facilitate their movement under water (Kurochkin, 1971;Ibáñez & Tambussi, 2012), the result of our study showed that covariant changes of the sternum and pelvis in these groups have opposite directions.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…This is most clearly seen in the case of wing-and foot-propelled underwater swimmers. Although both ecological groups share a number of distinctive features, such as posterior position of legs on a long axis of a body (Kurochkin, 1971;Johnsgard, 1987;Ibáñez & Tambussi, 2012), narrow elongated pelvis (Raikow, 1970(Raikow, , 1985Kurochkin, 1971;Bogdanovich, 2003), a great height of the acetabular zone (Ibáñez & Tambussi, 2012;Anten-Houston et al, 2017), low pelvic angles (Anten-Houston et al, 2017) that facilitate their movement under water (Kurochkin, 1971;Ibáñez & Tambussi, 2012), the result of our study showed that covariant changes of the sternum and pelvis in these groups have opposite directions.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we tried, fi rst of all, to evaluate the integration between diff erent locomotor modules, which has not previously been the subject of a special study in water birds. Studies of locomotion mechanisms in aquatic birds revealed a signifi cant variation in hindlimb movement patterns even among foot-propelled divers (Johansson & Norberg, 2003;Clift on & Biewener, 2018), which aff ects some structural features of both the pelvis and hind limbs (Kurochkin, 1971;Bogdanovich, 2014). Th ese data extend the understanding of pathways of narrow adaptations in water birds.…”
Section: Introductionmentioning
confidence: 91%
See 3 more Smart Citations